Efficient Development of Applied Technology Innovation Through Design For Manufacture and Assembly - Fathurrachman Batara Sulo, Andi; Fiqri Vigriawan Bataralipu, Andi; Ansori, Ansori (International Journal of Science, Technology & Management, 2023)
The conventional product design process and the design results from the designer need to be evaluated and optimized in terms of the manufacturing process and assembly process by the manufacturing department. In this process, it is sometimes necessary to make design changes that must be consulted with the designer to make it more efficient. This can be seen from three aspects of the product, namely quality, cost, and production time. A very applicable method to meet the needs of these 3 aspects of the product is the design method for manufacturing. One solution that can be applied is the design for manufacture and assembly (DFMA) method. DFMA is a method to evaluate the design of a product so that it can be easily assembled and manufactured. This paper will explain the application of the DFMA method to several applied technology product designs. As a case example for the application of the DFMA method, the development of a post-stroke bicycle frame from the initial design to the final design step, namely prototyping, is observed. A prototype was also evaluated with the help of the DFMA method and the evaluation results showed that the application of the DFM method provided significant improvements, where the total components of the bicycle frame at the beginning of the design were 53 pieces, in the final design could be reduced to 29 pieces (45%), with design efficiency increasing by 1.04%.